The Ambiguity of Using the Statement of Absolute Responsibility Based on Minister of Home Affairs Regulation Number 109 of 2019: Study in Dharmasraya Regency, West Sumatra Province, Indonesia - Nofialdi, Nofialdi; Elimartati, Elimartati; Iska, Syukri; Rizal, Deri; Firdaus, Firdaus; Kasmidin, Kasmidin; Hamdani, Hamdani (Al-Risalah, 2023)
Marriages are required to be registered under the provisions of Law Number 1 of 1974, specifically Article 2. This registration plays a crucial role in establishing the legality of marriages and enables the utilization of different associated benefits. Meanwhile, unregistered marriages give rise to a range of legal issues, including uncertainties regarding lineage, concerns related to maintenance, and inheritance rights. In line with the Ministry of Home Affairs Regulation Number 109 of 2019 regarding Population Administration, couples involved have the option to obtain important documents such as the Population Identification Card (KTP), Birth Certificate, and Family Card (KK) by signing a Statement of Absolute Responsibility (SPTJM). This situation raises significant concerns regarding the legal implications of unregistered marriages. Therefore, this study aimed to employ an empirical legal approach with qualitative methods and obtained data through interviews, observations, and documentation. The data analysis used Miles and Huberman's method to uncover the meaning within Ministry of Home Affairs Regulation Number 109 of 2019 regarding Unregistered Marriages and unveiled the ambiguity in understanding the true meaning. Furthermore, a study conducted in Dharmasraya Regency in 2021 discovered the issuance of 69,144 Family Cards by the Directorate General of Population and Civil Registration, and 22,453 (32.47%) were unregistered marriages. Only 194 individuals applied for validation (isbat) within 3 years, where 101, 27, and 66 were accepted, rejected, and revoked, respectively. In conclusion, the community perceived their marriages to be legal due to the issuance of Ministry of Home Affairs Regulation Number 109 of 2019, even though the SPTJM did not legalize the concept or hold legal authority over the consequences.